Heavy oil cracking catalyst and preparation method thereof
By using the titanium tetrachloride-containing waste liquid produced during the preparation of polypropylene catalyst to prepare a titanium-containing composite binder and mixing it with other components, a heavy oil cracking catalyst with excellent performance was prepared, which solved the complex problems of waste liquid treatment and catalyst preparation processes, and achieved efficient conversion and low coke growth effects.
Patent Information
- Application Number
- CN202311423636.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The large amount of waste liquid containing titanium tetrachloride produced during the preparation of polypropylene catalyst is difficult to handle, and the preparation process of the prior art titanium-containing kaolinite is complicated, requiring multiple addition of acid and filtration.
A waste liquid containing titanium tetrachloride is used to prepare a titanium-containing composite binder and is used to prepare a heavy oil cracking catalyst. By mixing it with clay, molecular sieve and other components, a catalyst with excellent performance is created.
The waste liquid containing titanium tetrachloride is effectively utilized, the catalyst preparation process is simplified, the production cost is reduced, the anti-wear performance and pore volume of the catalyst is improved, the efficient conversion of heavy oil is promoted, the tendency to coke is reduced, and the economic benefits of the catalytic cracking device are improved.
Smart Images

Figure BDA0004522786120000181 
Figure BDA0004522786120000191 
Figure BDA0004522786120000192
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oil refining catalysts and relates to a heavy oil cracking catalyst, in particular to a heavy oil cracking catalyst for reducing heavy oil yield and coke selectivity and a preparation method thereof. Background Art
[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, patent CN102336851B discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; patent CN107434832B discloses a propylene polymerization catalyst, mainly composed of alcohol magnesium compounds, titanium compounds and phosphate electron donor compounds. The common method for preparing titanium catalysts at present is: firstly prepare magnesium halide alcohol compound, for example, after magnesium halide and alcohol are heated and dissolved, high pressure ejection or high speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcohol compound particles are reacted with halogen-containing compounds such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the obtained solid catalyst component needs to be washed with a hydrocarbon solvent (such as hexane) to remove the unloaded titanium tetrachloride therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing at least one of titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, and unreacted esters will be produced. A large amount of waste liquid containing titanium tetrachloride is produced in the titanium-based polypropylene catalyst preparation process, which contains a small amount of alkoxy titanium complex (for example, about 2-5%), a small amount of lipids, and n-hexane in addition to titanium tetrachloride (at least 80%). If the waste liquid is directly discarded, it is bound to cause environmental pollution and waste of resources, so it is necessary to make effective use of it.
[0003] Regarding the preparation of titanium sol, titanium-containing molecular sieve, titanium-containing catalytic material, titanium-containing catalyst and additive from titanium tetrachloride, patent CN107866211B discloses a TiO2 sol and a catalytic cracking catalyst and their preparation methods, wherein the titanium-chlorine molar ratio of the TiO2 sol is (0.2-0.6): 1; and the corrosion rate of the TiO2 sol is ≤1g / m 2·h, pH value is 5-8, and viscosity at 20°C is ≥1000mPa·s. The provided TiO2 sol has the characteristics of high viscosity, low corrosion rate, and high pH value. When used as a binder for preparing a catalytic cracking catalyst, it is beneficial to increase the specific surface area of the catalytic cracking catalyst, improve the sphericity of the catalytic cracking catalyst, enhance the activity of the catalytic cracking catalyst, improve the product distribution of the catalytic cracking reaction, and is mainly beneficial to the generation of the target product gasoline.
[0004] Patent CN102114429B discloses a method for increasing the B acid content of ZSM-5 molecular sieve and increasing the production of light olefins. The method is to simultaneously modify the ZSM-5 molecular sieve with iron and titanium. After modification, the mass ratio of iron to titanium in the molecular sieve is 0.3-3:1, thereby improving the catalytic reactivity of the molecular sieve, promoting the conversion of long-chain alkanes and aromatics with long-chain alkyl side chains such as isopropylbenzene, and achieving the effect of significantly increasing the yield of light olefins.
[0005] Patent CN109694721B discloses a macroporous kaolinite and its preparation and application. The macroporous kaolinite contains a modified metal, and the average pore diameter is 2-50nm. The pore volume of pores with a pore diameter of 10-50nm accounts for more than 80% of the total pore volume. The modified metal is one or more of alkaline earth metals, titanium and zirconium. The preparation method of the macroporous kaolinite comprises: first calcining the kaolinite; forming a mixture of the kaolinite after the first calcination and the first acid, water, and an optional modified metal compound, performing a first treatment, then performing a second calcination, and then forming a mixture with the second acid, water, a pore expander and an optional modified metal compound for a second treatment, filtering and drying to obtain the macroporous kaolinite, and the modified metal compound is added in at least one step of the first treatment and the second treatment. The macroporous kaolinite can be used to prepare a cracking catalyst, and the obtained catalyst has high heavy oil conversion activity, high gasoline and liquefied gas yields, low dry gas selectivity, and low coke selectivity.
[0006] Patent CN105618107B discloses a catalytic cracking catalyst and a preparation method thereof. Based on the total weight of the catalyst, the catalyst contains 10-60wt% titanium and / or zirconium modified Y molecular sieve, 10-60wt% clay and 5-50wt% binder; the titanium and / or zirconium modified Y molecular sieve contains 1.0wt%-15.0wt% titanium and / or zirconium metal oxide. The catalyst preparation method comprises the steps of preparing titanium and / or zirconium modified Y molecular sieve, preparing catalyst slurry and spray drying, wherein the titanium and / or zirconium modified Y molecular sieve comprises the following steps: (1) dispersing a titanium and / or zirconium-containing compound in water, and adjusting the pH value of the mixture to 3-10; (2) mixing the molecular sieve with the mixture obtained in step (1), stirring; optionally filtering and / or drying; (3) calcining at 300-700°C. The catalyst has a high heavy oil conversion capacity and gasoline yield.
[0007] The prior art does not involve the treatment of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts. Moreover, the preparation process of titanium-containing kaolinite is complicated, and acid needs to be added and filtered multiple times during the preparation process.
[0008] Therefore, in order to solve the problem of treating a large amount of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts and to solve the unfavorable factors of high heavy oil yield and high coke generation during heavy oil cracking, despite the recent catalyst technology, new technology for preparing heavy oil cracking catalysts with simple and feasible preparation process and excellent performance is still needed. Summary of the invention
[0009] In order to solve the above problems, the purpose of the present invention is to provide a heavy oil cracking catalyst and a preparation method thereof, which can promote the efficient conversion of heavy oil, reduce the tendency to coke, have excellent reaction selectivity and performance, improve the economic benefits of the catalytic cracking unit, and reduce the carbon emissions of the catalytic cracking unit.
[0010] In order to achieve the above object, the present invention provides a heavy oil cracking catalyst, which, based on the weight of the heavy oil cracking catalyst being 100%, comprises: 0-10% of ZSM-5 molecular sieve on a dry basis, 15-50% of Y-type molecular sieve on a dry basis, 10-55% of clay on a dry basis, 0-30% of pseudo-boehmite on a dry basis, 4-70% of titanium-containing composite binder on a dry basis, 0-15% of binder on an oxide basis, 0-30% of inorganic oxide carrier material on an oxide basis, and 0.2-5% of modified metal compound; wherein the preparation method of the titanium-containing composite binder comprises the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the mixture at 40-120° C. for 0.5-6 h to obtain the titanium-containing composite binder; based on the dry basis of the titanium-containing composite binder as 100%, the composition of the titanium-containing composite binder comprises 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide, and 30-92wt% silicon calculated as oxide.
[0011] According to a specific embodiment of the present invention, preferably, based on the weight of the heavy oil cracking catalyst being 100%, its composition comprises: 1-8% of ZSM-5 molecular sieve on a dry basis, 20-45% of Y-type molecular sieve on a dry basis, 10-45% of clay on a dry basis, 5-25% of pseudo-boehmite on a dry basis, 6-55% of titanium-containing composite binder on a dry basis, 3-15% of binder on an oxide basis, 2-15% of inorganic oxide support material on an oxide basis, and 0.5-3% of modified metal compound on an oxide basis.
[0012] According to a specific embodiment of the present invention, preferably, the solid content of the titanium-containing composite binder is 10-45wt%.
[0013] According to a specific embodiment of the present invention, preferably, based on the dry basis of the titanium-containing composite binder being 100%, the composition of the titanium-containing composite binder comprises 7-30wt% titanium calculated as oxide, 8-40wt% aluminum calculated as oxide, and 35-70wt% silicon calculated as oxide.
[0014] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, the mixed raw materials also include a dispersant.
[0015] According to a specific embodiment of the present invention, preferably, the content of the dispersant is less than 10% based on the dry basis of the titanium-containing composite binder being 100%.
[0016] According to a specific embodiment of the present invention, preferably, the content of the dispersant is 0.3-5%.
[0017] According to a specific embodiment of the present invention, preferably, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0018] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, the titanium tetrachloride solution is titanium tetrachloride waste liquid; more preferably, the titanium tetrachloride waste liquid is a titanium tetrachloride-containing waste liquid generated in the preparation process of a polypropylene catalyst, and the titanium of the titanium-containing composite binder comes from the titanium tetrachloride-containing waste liquid generated in the preparation process of a polypropylene catalyst.
[0019] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, the titanium tetrachloride solution is pure titanium tetrachloride.
[0020] According to a specific embodiment of the present invention, preferably, in the preparation method of the titanium-containing composite binder, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite; more preferably, the clay is one or a combination of two or more of kaolin, halloysite, diatomaceous earth, halloysite and sepiolite.
[0021] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, the calcination is performed at 400-900° C. for 0.5-6 h.
[0022] According to a specific embodiment of the present invention, preferably, the preparation method of the titanium-containing composite binder comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the titanium-containing composite binder.
[0023] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8, and more preferably, the pH value of the reaction system is adjusted to 0.5-8 using an alkaline substance.
[0024] According to a specific embodiment of the present invention, preferably, in step (1), the clay is crushed to an average particle size D (v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
[0025] According to a specific embodiment of the present invention, preferably, the alkaline substance is selected from one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, sodium aluminate, magnesium oxide, magnesium hydroxide, magnesium carbonate, calcium oxide, calcium hydroxide and calcium carbonate.
[0026] According to a specific embodiment of the present invention, the ZSM-5 molecular sieve contains 0.2-6% phosphorus and 0-5% of a second element, calculated as oxide, wherein the second element includes one or a combination of two or more of iron, zinc, magnesium, calcium, titanium, zirconium, lanthanum, cerium and yttrium.
[0027] According to a specific embodiment of the present invention, preferably, the Y-type molecular sieve includes one or a combination of two or more of HY, NH4Y, hydrothermal ultra-stable Y molecular sieve, silicon tetrachloride vapor phase ultra-stable Y molecular sieve, rare earth-containing Y-type molecular sieve, and phosphorus-modified ultra-stable Y molecular sieve.
[0028] According to a specific embodiment of the present invention, preferably, the rare earth-containing Y-type molecular sieve comprises one or a combination of two of a rare earth-modified ultrastable Y-type molecular sieve and an ultrastable Y-type molecular sieve modified with phosphorus and rare earth.
[0029] According to a specific embodiment of the present invention, preferably, the clay comprises one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite, and more preferably, the clay comprises one or a combination of two or more of kaolin, halloysite, diatomaceous earth, halloysite and sepiolite.
[0030] According to a specific embodiment of the present invention, preferably, the binder includes one or a combination of two or more of aluminum sol, silica sol, silica-aluminum sol, and phospho-aluminum sol.
[0031] According to a specific embodiment of the present invention, preferably, the inorganic oxide carrier material includes one or a combination of two or more of white carbon black, an alumina material containing a Br(II) acid center, and a silica-alumina material containing a Br(II) acid center; the alumina material containing a Br(II) acid center and the silica-alumina material containing a Br(II) acid center have a high pore volume, a large specific surface area, a double pore distribution, a high thermal stability and a higher acid amount, and contain a Br(II) acid center.
[0032] According to a specific embodiment of the present invention, preferably, the modified metal compound includes one or a combination of two or more of oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of zinc, magnesium, calcium, titanium, zirconium, lanthanum, cerium and yttrium.
[0033] According to a specific embodiment of the present invention, preferably, the composition of the heavy oil cracking catalyst further includes a pore structure improver.
[0034] According to a specific embodiment of the present invention, preferably, the weight of the pore structure improver is 0.1-10% of the total weight of the heavy oil cracking catalyst, and more preferably 0.3-5%; the pore structure improver is added during the catalyst preparation process (the addition amount is, for example, 0.3-6%) to improve the pore structure, specific surface area and other properties of the catalyst.
[0035] According to a specific embodiment of the present invention, preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0036] The titanium-containing composite binder in the heavy oil cracking catalyst raw material of the present invention is prepared by calcining clay at high temperature, wherein the crystal structure thereof changes. For example, the silicon and aluminum contained in kaolin are mainly kaolinite structures. After calcining at high temperature, kaolinite undergoes a phase transformation to form active silicon and active aluminum, which can react with acid or alkali; titanium tetrachloride is hydrolyzed to produce titanium oxide and hydrogen chloride. The above properties of clay and titanium tetrachloride are utilized, and waste liquid containing titanium tetrachloride is used to treat the calcined clay. The calcined clay is mixed with water and waste liquid containing titanium tetrachloride, and the hydrochloric acid produced by the hydrolysis of titanium tetrachloride reacts with the active aluminum in the calcined clay to prepare a composite binder containing titanium and clay. Since the active aluminum in the clay reacts with the hydrochloric acid produced by the hydrolysis of titanium tetrachloride, the active aluminum is separated from the clay, and medium and large pores are formed in the clay. At the same time, the active aluminum reacting with the hydrochloric acid and the fine titanium oxide particles produced by the hydrolysis jointly form a titanium-aluminum mixture, and together with the medium and large pore clay, a composite binder containing titanium and clay is formed. This titanium-containing composite binder has the function of a binder and contains medium and large pore clay components, which is beneficial to improving the pore structure of the catalyst, increasing the proportion of medium and large pores of the catalyst, and improving the diffusion performance.
[0037] The present invention also provides a method for preparing the heavy oil cracking catalyst, which comprises the following steps: (1) mixing and slurrying the ZSM-5 molecular sieve, Y-type molecular sieve, clay, pseudo-boehmite, inorganic oxide carrier material, titanium-containing composite binder, binder, and modified metal compound (preferably with a pore structure improver) to obtain a slurry; (2) spray-drying the slurry to form it, then calcining and curing it, washing and reducing sodium, and drying it to obtain the heavy oil cracking catalyst.
[0038] According to a specific embodiment of the present invention, preferably, the molecular sieve in step (1) is sand-milled before mixing and slurrying and / or the slurry in step (2) is sand-milled before spray drying, so that the average particle size D (v, 0.5) of the molecular sieve in step (1) and / or the slurry in step (2) is less than 4 μm.
[0039] According to a specific embodiment of the present invention, preferably, the average particle size D (v, 0.5) of the slurry is less than 4 μm.
[0040] According to a specific embodiment of the present invention, preferably, the pseudo-boehmite is acidified and then aged at 40-90° C. for 0.5-3 hours before being peptized for use.
[0041] According to a specific embodiment of the present invention, preferably, in the acid peptization process of pseudo-boehmite, the acid is an inorganic acid, more preferably one or a combination of two or more of hydrochloric acid, sulfuric acid and nitric acid.
[0042] According to a specific embodiment of the present invention, preferably, the pseudo-boehmite is first mixed with a titanium-containing composite binder, aged at 40-90° C. for 0.5-3 hours for peptization, and then used.
[0043] According to a specific embodiment of the present invention, preferably, the ZSM-5 molecular sieve is a mesoporous ZSM-5 molecular sieve.
[0044] The present invention does not limit the spray drying method, and the technology known to those skilled in the art can be used, and the process conditions are, for example, the spray tower furnace temperature is controlled at 450-550° C., and the spray tail gas temperature is controlled at 200-300° C. The present invention can control the screening distribution of the spray-formed catalyst microspheres by controlling the spray forming conditions such as the spray pressure and the nozzle size.
[0045] Waste liquid containing titanium tetrachloride generated in the process of preparing polypropylene catalyst contains about 80%-95% titanium tetrachloride (by weight). If it is discharged into the environment, it will inevitably cause environmental pollution and waste of resources. The present invention uses the waste liquid containing titanium tetrachloride generated in the process of preparing polypropylene catalyst to prepare a composite binder containing titanium and clay and to prepare a catalytic cracking catalyst, which not only solves the problem of using the waste liquid containing titanium tetrachloride, avoids the pollution of the environment, reduces the high cost of treating the waste liquid, but also avoids the shortcomings of the prior art. The preparation process of the titanium-containing composite binder is simple and feasible, the pH value is adjustable, and the titanium content can be adjusted in a large range.
[0046] The heavy oil cracking catalyst of the present invention has a simple and feasible preparation process, and the titanium content can be adjusted within a relatively large range; the prepared heavy oil cracking catalyst can be used in a catalytic cracking unit, has excellent anti-wear performance and a relatively large pore volume, and is used in the heavy oil cracking process to promote the efficient conversion of heavy oil, reduce the heavy oil yield, and reduce the tendency to form coke, has excellent reaction selectivity and use performance, improves the economic benefits of the catalytic cracking unit, and reduces the carbon emissions of the catalytic cracking unit. DETAILED DESCRIPTION
[0047] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0048] The element contents in the following samples and catalysts were determined by X-ray fluorescence analysis. The wear index of the catalyst was analyzed by MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd. The pore volume of the catalyst was determined by the water drop method.
[0049] The origin and specifications of the raw materials used are as follows:
[0050] (1) Waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalyst (hereinafter referred to as waste liquid containing titanium tetrachloride): titanium content 90% (calculated as TiCl4), provided by Lanzhou Chemical Research Center of PetroChina Petrochemical Research Institute; kaolin (burn-off 29 wt%), halloysite (burn-off 16.6 wt%), pseudo-boehmite (burn-off 36 wt%), aluminum sol (containing 21.6 wt% alumina), ordinary ZSM-5 molecular sieve (silicon-aluminum ratio 31, mesoporous volume 0.04 mL / g), REHY molecular sieve (Na2O content 1.2 wt%, RE2O3 content 8.3 wt%, reduced by 4 wt%), GUSY-1 molecular sieve (silicon tetrachloride vapor phase ultra-stable molecular sieve, Na2O content 1.2 wt%, RE2O3 content 2.5 wt%, relative crystallinity 57%, unit cell constant Reduce by 15wt%), REUSY molecular sieve (Na2O content 1.4wt%, RE2O3 content 2.3wt%, reduce by 5wt%), rare earth chloride solution (RE2O3 content 289.3g / L): all are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.
[0051] (2) Mesoporous ZSM-5 molecular sieve: Si / Al ratio 30, mesopore volume 0.29 mL / g;
[0052] (3) Diatomaceous earth (ignition loss 2.6wt%): industrial product;
[0053] (4) Titanium tetrachloride, oxalic acid, magnesium chloride, magnesium oxide, cerium oxide, yttrium nitrate, yttrium oxide, zirconium oxide, polyethylene glycol, carboxymethyl cellulose: all are chemical reagents;
[0054] (5) Hydrochloric acid: concentration 36%, chemical reagent; nitric acid: concentration 65-68%, chemical reagent; ammonia water: concentration 18%, chemical reagent.
[0055] The spray drying methods of the heavy oil cracking catalysts of the following Examples 1-7 and Comparative Examples 1-9 adopt the following process conditions: the furnace temperature of the spray tower is controlled at 450°C, the spray tail gas temperature is controlled at 200°C, and the particle size range of the obtained catalyst is 65-78 μm.
[0056] Example 1
[0057] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0058] (1) Preparation of titanium-clay composite binder:
[0059] Kaolin was calcined at 750°C for 2 hours to obtain a calcined material. 1674 g (dry basis) of the calcined material was crushed to an average particle size D (v, 0.5) < 4 μm, 5.16 L of decationized water was added and stirred, 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added, the temperature was raised to 70°C, and stirred for 1 hour. The pH value was 3.5 to obtain a composite binder M-1 containing titanium and clay.
[0060] The composition of the composite binder M-1 containing titanium and clay is: 93wt% (dry basis) of kaolin roasted material, 7wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-1 is 25wt%.
[0061] (2) Preparation of heavy oil cracking catalyst:
[0062] 1.524 kg of halloysite (on a dry basis), 1.68 kg of composite binder M-1, 0.15 kg of alumina sol (on alumina basis), 72.6 mL of rare earth chloride solution and 0.54 kg of deionized water were added to a beating tank for beating;
[0063] 0.84 kg of REUSY molecular sieve (dry basis), 152.5 g of yttrium nitrate and 1.29 kg of deionized water were mixed and beaten for 1.5 hours, and then added to the first step beating tank, and then 30 g of carboxymethyl cellulose was added, and the beating was carried out for 2 hours. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0064] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-1.
[0065] The composition of the heavy oil cracking catalyst CAT-1 is: 50.8wt% (dry basis) of halloysite, 14wt% (dry basis) of solids from the composite binder M-1, 5wt% of alumina from aluminum sol, 28wt% (dry basis) of REUSY molecular sieve, 1.5wt% of yttrium oxide from yttrium nitrate, 0.7wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 42%.
[0066] Example 2
[0067] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0068] (1) Preparation of titanium-clay composite binder:
[0069] The halloysite was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600°C for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material was added to 7.3 L of decationized water and stirred, and 793 g of waste liquid containing titanium tetrachloride was added. The temperature was raised to 90°C and stirred for 2 hours. The pH value was adjusted to 2.5 with ammonia water to obtain a composite binder M-2 containing titanium and clay.
[0070] The composition of the composite binder M-2 containing titanium and clay is: 83.3wt% (dry basis) of halloysite calcined material, 16.7wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-2 is 18wt%.
[0071] (2) Preparation of heavy oil cracking catalyst:
[0072] 0.675 kg of kaolin (dry basis) and 5 kg of composite binder M-2 were added to a beating tank for beating, and then 0.36 kg of pseudo-boehmite (dry basis) and 155.5 mL of rare earth chloride solution were added, stirred for 1.5 h, and then 42 mL of hydrochloric acid was added, stirred for 0.5 h, and then aged at 50 ° C for 1 h;
[0073] 0.9 kg of GUSY-1 molecular sieve (dry basis), 60 g of common ZSM-5 molecular sieve (dry basis), 60 g of yttrium oxide and 1.5 kg of deionized water were mixed and beaten for 0.5 h, then added to the first step beating tank, and then 15 g of polyethylene glycol was added, and the beating was continued for 1 h. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and then spray-dried to obtain catalyst microspheres;
[0074] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-2.
[0075] The composition of the heavy oil cracking catalyst CAT-2 is: 22.5wt% (dry basis) of kaolin, 12wt% of alumina from pseudo-boehmite, 30wt% (dry basis) of solids from the composite binder M-2, 30wt% (dry basis) of GUSY-1 molecular sieve, 2wt% (dry basis) of ordinary ZSM-5 molecular sieve, 2wt% of yttrium oxide, 1.5wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 32%.
[0076] Example 3
[0077] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0078] (1) Preparation of titanium-clay composite binder:
[0079] Kaolin and diatomaceous earth were respectively crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2.5 hours to obtain a calcined material. 900 g (dry basis) of kaolin calcined material, 100.8 g (dry basis) of diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose were added to 2.0 L of decationized water and stirred. 2109 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 60°C, stirred for 3 hours, and the pH value was adjusted to 3.0 with ammonia water to obtain a composite binder M-3 containing titanium and clay.
[0080] The composition of the titanium-clay-containing composite binder M-3 is: 50wt% (dry basis) of kaolin calcined material, 5.6wt% (dry basis) of diatomaceous earth calcined material, 44.4wt% (calculated as titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-3 is 30wt%.
[0081] (2) Preparation of heavy oil cracking catalyst:
[0082] 0.645 kg kaolin (dry basis), 0.18 kg diatomaceous earth (dry basis), 0.24 kg (solid content) composite binder M-3, 0.18 kg (alumina) aluminum sol, 15 g cerium oxide, 45 g zirconium oxide and 1.53 kg deionized water were added to a beating tank for beating, and then 0.54 kg pseudo-boehmite (dry basis) was added and stirred for 1 hour, and then 30 mL nitric acid was added, stirred for 1 hour, and then aged at 50° C. for 1.2 hours;
[0083] 0.72 kg of GUSY-1 molecular sieve (dry basis), 0.18 kg of REHY molecular sieve (dry basis), 0.24 kg (dry basis) of mesoporous ZSM-5 molecular sieve, 76.2 g of magnesium chloride and 1.74 kg of deionized water were mixed and beaten for 0.5 h, then added to the first beating tank, and then 150 g of carboxymethyl cellulose was added, and the beating was performed for 1.8 h. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0084] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-3.
[0085] The composition of the heavy oil cracking catalyst CAT-3 is: 21.5wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomaceous earth, 18wt% of alumina from pseudo-boehmite, 8wt% (dry basis) of solids from composite binder M-3, 6wt% (dry basis) of alumina from aluminum sol, 24wt% (dry basis) of GUSY-1 molecular sieve, 6wt% (dry basis) of REHY molecular sieve, 8wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 1.5wt% of zirconium oxide, 0.5wt% of cerium oxide, 0.5wt% of magnesium oxide from magnesium chloride, and the solid content of the catalyst gel is 36%.
[0086] Example 4
[0087] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0088] (1) Preparation of titanium-clay composite binder:
[0089] The kaolin was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2 hours to obtain a calcined material. 1674 g (dry basis) of the calcined material was added to 5.19 L of decationized water and stirred, 299 g of titanium tetrachloride and 9 g of polyethylene glycol were added, the temperature was raised to 85°C, and stirred for 4 hours. The pH value was 3.6 to obtain the titanium-clay composite binder M-4.
[0090] The composition of the composite binder M-4 containing titanium and clay is: 93wt% (dry basis) of kaolin calcined material, 7wt% (titanium oxide) of titanium from titanium tetrachloride, and the solid content of the composite binder M-4 is 25wt%.
[0091] (2) Preparation of heavy oil cracking catalyst:
[0092] 0.9 kg of halloysite (on a dry basis), 0.75 kg of kaolin (on a dry basis), 0.48 kg of composite binder M-4, 0.414 kg of alumina sol (on alumina basis), 20.7 mL of rare earth chloride solution and 0.82 kg of deionized water were added to a beating tank for beating;
[0093] 0.45 kg of REUSY molecular sieve (dry basis), 0.3 kg (dry basis) of mesoporous ZSM-5 molecular sieve, 203.4 g of yttrium nitrate and 1.13 kg of deionized water were mixed and beaten for 1 hour, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added and beaten for 0.5 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0094] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-4.
[0095] The composition of the heavy oil cracking catalyst CAT-4 is: 30wt% (dry basis) of halloysite, 25wt% (dry basis) of kaolin, 4wt% (dry basis) of solids from the composite binder M-4, 13.8wt% of alumina from aluminum sol, 15wt% (dry basis) of REUSY molecular sieve, 10wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 2wt% of yttrium oxide from yttrium nitrate, 0.2wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 40%.
[0096] Example 5
[0097] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0098] Add 11.67 kg of composite binder M-2 and 51.8 mL of rare earth chloride solution into a pulping tank for pulping;
[0099] 0.84 kg of GUSY-1 molecular sieve (dry basis) and 45 g of yttrium oxide were added to the first step beating tank, and then 3 g of polyethylene glycol was added, and the beating was performed for 1 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0100] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-5.
[0101] The composition of the heavy oil cracking catalyst CAT-5 is: 70wt% (dry basis) of solids from the composite binder M-2, 28wt% (dry basis) of GUSY-1 molecular sieve, 1.5wt% of yttrium oxide, 0.5wt% of rare earth oxide from rare earth chloride solution, and 21.3% of catalyst gel solid content.
[0102] Example 6
[0103] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0104] 0.84 kg kaolin (dry basis), 0.72 kg composite binder M-1, 0.9 kg pseudo-boehmite (dry basis), 39 g cerium oxide and 3.40 kg deionized water were added to a beating tank for beating, and then 45 mL hydrochloric acid was added, stirred for 0.5 h, and aged at 60 ° C for 0.5 h;
[0105] 0.9 kg of REUSY molecular sieve (dry basis), 30 g (dry basis) of mesoporous ZSM-5 molecular sieve, 90 g of yttrium oxide, 21 g of magnesium oxide and 1.47 kg of deionized water were mixed and beaten for 0.5 h, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added and beaten for 0.5 h. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0106] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-6.
[0107] The composition of the heavy oil cracking catalyst CAT-6 is: 28wt% (dry basis) of kaolin, 6wt% (dry basis) of solids from the composite binder M-1, 30wt% of alumina from pseudo-boehmite, 30wt% (dry basis) of REUSY molecular sieve, 1wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 3wt% of yttrium oxide, 1.3wt% of cerium oxide, 0.7wt% of magnesium oxide, and the solid content of the catalyst gel is 32%.
[0108] Example 7
[0109] This embodiment provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0110] 0.57 kg kaolin (dry basis), 1.667 kg composite binder M-2, 0.45 kg aluminum sol (alumina basis), 0.12 kg pseudo-boehmite (dry basis), and 30 g cerium oxide were added to a beating tank for beating, and then 6 mL hydrochloric acid was added, stirred for 0.5 h, and aged at 60° C. for 0.5 h;
[0111] 1.5 kg of GUSY-1 molecular sieve (dry basis), 101.7 g of yttrium nitrate and 2.35 kg of deionized water were mixed and beaten for 1 hour, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added, and the beating was performed for 0.5 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0112] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst CAT-7.
[0113] The composition of the heavy oil cracking catalyst CAT-7 is: 19wt% kaolin (dry basis), 4wt% alumina from pseudo-boehmite, 10wt% solids from the composite binder M-2 (dry basis), 15wt% alumina from aluminum sol, 50wt% GUSY-1 molecular sieve (dry basis), 1wt% yttrium oxide from yttrium nitrate, 1wt% cerium oxide, and the solid content of the catalyst gel is 34%.
[0114] Comparative Example 1
[0115] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0116] (1) A macroporous kaolinite, which is prepared according to the method of Example 8 of preparing macroporous kaolinite disclosed in CN109694721B. The specific preparation method is as follows:
[0117] The kaolin was calcined at 750°C for 2 hours to obtain a calcined material (referred to as the first calcined material). 1680 g (dry basis) of the calcined material was added with decationized water (pH=3.1, the same below) and stirred to prepare a slurry with a solid content of 25 wt%. 5000 g of 1 mol / L hydrochloric acid and 1000 g of oxalic acid and 120 g of TiCl4 (analytical grade) were added. The temperature was raised to 70°C and stirred for 1 hour. The mother liquor was then filtered out and the filter cake was dried to obtain the first step product. 1200 g of the product was calcined at 750°C for 2 hours to obtain a calcined material (referred to as the second calcined material). 1000 g (dry basis) of the second calcined material was added with decationized water and stirred to obtain a slurry with a solid content of 25 wt%. 2000 g of 1 mol / L hydrochloric acid, 500 g of oxalic acid, 500 g of polyethylene glycol, and 70 g of TiCl4 (analytical grade) were added. The temperature was raised to 70°C and stirred for 1 hour. The mother liquor was then filtered out and the filter cake was dried to obtain macroporous kaolinite DM-1.
[0118] (2) Preparation of heavy oil cracking catalyst:
[0119] 1.434 kg of halloysite (on a dry basis), 0.42 kg of macroporous kaolinite DM-1 (on a dry basis), 0.24 kg of alumina sol (on alumina basis), 72.6 mL of rare earth chloride solution and 0.44 kg of deionized water were added to a beating tank for beating;
[0120] 0.84 kg of REUSY molecular sieve (dry basis), 152.5 g of yttrium nitrate and 1.29 kg of deionized water were mixed and slurried for 1.5 hours, and then added to the first slurrying tank and slurried for 2 hours. The obtained slurry was homogenized and spray-dried to obtain catalyst microspheres;
[0121] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-1.
[0122] The composition of the heavy oil cracking catalyst DCAT-1 is: 47.8wt% (dry basis) of halloysite, 14wt% (dry basis) of macroporous kaolinite DM-1, 8wt% of alumina from aluminum sol, 28wt% (dry basis) of REUSY molecular sieve, 1.5wt% of yttrium oxide from yttrium nitrate, 0.7wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 42%.
[0123] Comparative Example 2
[0124] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0125] (1) A modified halloysite, the preparation method of which is as follows:
[0126] The halloysite was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600°C for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material was added with 5.3 L of decationized water and stirred, and 1526 g of hydrochloric acid was added, and the temperature was raised to 90°C and stirred for 2 hours to obtain modified halloysite DM-2. The solid content of the modified halloysite DM-2 was 18 wt%.
[0127] (2) Preparation of heavy oil cracking catalyst:
[0128] 0.675 kg of kaolin (dry basis) and 5 kg of modified halloysite DM-2 were added to a slurrying tank for slurrying, and then 0.36 kg of pseudo-boehmite (dry basis) and 155.5 mL of rare earth chloride solution were added, stirred for 1.5 h, and then 42 mL of hydrochloric acid was added, stirred for 0.5 h, and then aged at 50 ° C for 1 h;
[0129] 0.9 kg of GUSY-1 molecular sieve (dry basis), 60 g of common ZSM-5 molecular sieve (dry basis), 60 g of yttrium oxide and 1.5 kg of deionized water were mixed and beaten for 0.5 h, then added to the first step beating tank and beaten for 1 h. The resulting slurry was homogenized and spray dried to obtain catalyst microspheres;
[0130] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-2.
[0131] The composition of the heavy oil cracking catalyst DCAT-2 is: 22.5wt% (dry basis) of kaolin, 12wt% of alumina from pseudo-boehmite, 30wt% (dry basis) of modified halloysite DM-2, 30wt% (dry basis) of GUSY-1 molecular sieve, 2wt% (dry basis) of ordinary ZSM-5 molecular sieve, 2wt% of yttrium oxide, 1.5wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 32%.
[0132] Comparative Example 3
[0133] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0134] 1.395 kg of kaolin (on a dry basis) and 0.18 kg (on alumina basis) of aluminum sol were added to a slurrying tank for slurrying, and then 0.36 kg of pseudo-boehmite (on a dry basis) and 155.5 mL of rare earth chloride solution were added, stirred for 1.5 h, and then 42 mL of hydrochloric acid was added, stirred for 0.5 h, and then aged at 50 ° C for 1 h;
[0135] 0.9 kg of GUSY-1 molecular sieve (dry basis), 60 g of common ZSM-5 molecular sieve (dry basis), 60 g of yttrium oxide and 1.5 kg of deionized water were mixed and beaten for 0.5 h, then added to the first step beating tank and beaten for 1 h. The resulting slurry was homogenized and spray dried to obtain catalyst microspheres;
[0136] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-3.
[0137] The composition of the heavy oil cracking catalyst DCAT-3 is: 46.5wt% (dry basis) of kaolin, 12wt% of alumina from pseudo-boehmite, 6wt% (dry basis) of alumina from aluminum sol, 30wt% (dry basis) of GUSY-1 molecular sieve, 2wt% (dry basis) of ordinary ZSM-5 molecular sieve, 2wt% of yttrium oxide, 1.5wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 32%.
[0138] Comparative Example 4
[0139] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0140] (1) A comparative binder containing titanium and clay without calcination, the preparation method of which is as follows:
[0141] 1674 g (dry basis) of kaolin was pulverized to an average particle size D (v, 0.5) < 4 μm, and 4.2 L of decationized water was directly added without calcination and stirred. 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added. The temperature was raised to 70°C and stirred for 1 hour. The pH value was adjusted to 3.5 with ammonia water to obtain a comparative binder DM-3 containing titanium and clay.
[0142] The composition of the comparative binder DM-3 containing titanium and clay is: 93wt% kaolin (on a dry basis), 7wt% titanium from a waste liquid containing titanium tetrachloride (on a titanium oxide basis), and the solid content of the comparative binder DM-3 is 25wt%.
[0143] (2) Preparation of heavy oil cracking catalyst:
[0144] 1.524 kg of halloysite (on a dry basis), 1.68 kg of comparative binder DM-3, 0.15 kg of alumina sol (on alumina basis), 72.6 mL of rare earth chloride solution and 0.54 kg of deionized water were added to a beating tank for beating;
[0145] 0.84 kg of REUSY molecular sieve (dry basis), 152.5 g of yttrium nitrate and 1.29 kg of deionized water were mixed and beaten for 1.5 hours, and then added to the first step beating tank, and then 30 g of carboxymethyl cellulose was added, and the beating was carried out for 2 hours. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0146] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-4.
[0147] The composition of the heavy oil cracking catalyst DCAT-4 is: 50.8wt% (dry basis) of halloysite, 14wt% (dry basis) of solids from the comparative binder DM-3, 5wt% of alumina from aluminum sol, 28wt% (dry basis) of REUSY molecular sieve, 1.5wt% of yttrium oxide from yttrium nitrate, 0.7wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 42%.
[0148] Comparative Example 5
[0149] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0150] (1) A comparative binder containing titanium and clay:
[0151] Comparative binder DM-4 was prepared according to the method of composite binder M-3 containing titanium and clay in Example 3, except that ammonia water was not used to adjust the pH value. The preparation method is as follows:
[0152] Kaolin and diatomaceous earth were respectively crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2.5 hours to obtain a calcined material. 900 g (dry basis) of kaolin calcined material, 100.8 g (dry basis) of diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose were added to 2.0 L of decationized water and stirred, and 2109 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 60°C, and stirred for 3 hours to obtain a comparative binder DM-4 containing titanium and clay.
[0153] The composition of the comparative binder DM-4 containing titanium and clay is: 50 wt% (dry basis) of calcined kaolin, 5.6 wt% (dry basis) of calcined diatomaceous earth, and 44.4 wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride.
[0154] (2) Preparation of heavy oil cracking catalyst:
[0155] 0.645 kg kaolin (dry basis), 0.18 kg diatomaceous earth (dry basis), 0.24 kg (solid content) of comparative binder DM-4, 0.18 kg (alumina) of aluminum sol, 15 g cerium oxide, 45 g zirconium oxide and 1.53 kg of deionized water were added to a beating tank for beating, and then 0.54 kg of pseudo-boehmite (dry basis) was added, stirred for 1 hour, and then 30 mL of nitric acid was added, stirred for 1 hour, and then aged at 50° C. for 1.2 hours;
[0156] 0.72 kg of GUSY-1 molecular sieve (dry basis), 0.18 kg of REHY molecular sieve (dry basis), 0.24 kg (dry basis) of mesoporous ZSM-5 molecular sieve, 76.2 g of magnesium chloride and 1.74 kg of deionized water were mixed and beaten for 0.5 h, then added to the first beating tank, and then 150 g of carboxymethyl cellulose was added, and the beating was performed for 1.8 h. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0157] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-5.
[0158] The composition of the heavy oil cracking catalyst DCAT-5 is: 21.5wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomaceous earth, 18wt% of alumina from pseudo-boehmite, 8wt% (dry basis) of solids from the comparative binder DM-4, 6wt% (dry basis) of alumina from aluminum sol, 24wt% (dry basis) of GUSY-1 molecular sieve, 6wt% (dry basis) of REHY molecular sieve, 8wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 1.5wt% of zirconium oxide, 0.5wt% of cerium oxide, 0.5wt% of magnesium oxide from magnesium chloride, and the solid content of the catalyst gel is 36%.
[0159] Comparative Example 6 (Compared with Example 4)
[0160] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0161] 0.9 kg of halloysite (on a dry basis), 0.84 kg of kaolin (on a dry basis), 0.444 kg of alumina sol (on alumina basis), 20.7 mL of rare earth chloride solution and 1.03 kg of deionized water were added to a beating tank for beating;
[0162] 0.45 kg of REUSY molecular sieve (dry basis), 0.3 kg (dry basis) of mesoporous ZSM-5 molecular sieve, 203.4 g of yttrium nitrate and 1.13 kg of deionized water were mixed and beaten for 1 hour, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added and beaten for 0.5 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0163] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-6.
[0164] The composition of the heavy oil cracking catalyst DCAT-6 is: 30wt% (dry basis) of halloysite, 28wt% (dry basis) of kaolin, 14.8wt% of alumina from aluminum sol, 15wt% (dry basis) of REUSY molecular sieve, 10wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 2wt% of yttrium oxide from yttrium nitrate, 0.2wt% of rare earth oxide from rare earth chloride solution, and the solid content of the catalyst gel is 40%.
[0165] Comparative Example 7 (Compared with Example 5)
[0166] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0167] Add 2.1 kg of kaolin (dry basis), 51.8 mL of rare earth chloride solution and 8.71 kg of deionized water into a pulping tank for pulping;
[0168] 0.84 kg of GUSY-1 molecular sieve (dry basis) and 45 g of yttrium oxide were added to the first step beating tank, and then 3 g of polyethylene glycol was added, and the beating was performed for 1 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0169] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-7.
[0170] The composition of the heavy oil cracking catalyst DCAT-7 is: 70wt% (dry basis) of kaolin, 28wt% (dry basis) of GUSY-1 molecular sieve, 1.5wt% of yttrium oxide, 0.5wt% of rare earth oxide from rare earth chloride solution, and 21.3% of the solid content of the catalyst gel.
[0171] Comparative Example 8 (Compared with Example 6)
[0172] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0173] 1.02 kg kaolin (dry basis), 0.9 kg pseudo-boehmite (dry basis), 39 g cerium oxide and 3.87 kg deionized water were added to a pulping tank for pulping, and then 45 mL hydrochloric acid was added, stirred for 0.5 h, and aged at 60 ° C for 0.5 h;
[0174] 0.9 kg of REUSY molecular sieve (dry basis), 30 g (dry basis) of mesoporous ZSM-5 molecular sieve, 90 g of yttrium oxide, 21 g of magnesium oxide and 1.47 kg of deionized water were mixed and beaten for 0.5 h, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added and beaten for 0.5 h. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0175] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-8.
[0176] The composition of the heavy oil cracking catalyst DCAT-8 is: 34wt% (dry basis) of kaolin, 30wt% (dry basis) of alumina from pseudo-boehmite, 30wt% (dry basis) of REUSY molecular sieve, 1wt% (dry basis) of mesoporous ZSM-5 molecular sieve, 3wt% (dry basis) of yttrium oxide, 1.3wt% of cerium oxide, 0.7wt% of magnesium oxide, and the solid content of the catalyst gel is 32%.
[0177] Comparative Example 9 (Compared with Example 7)
[0178] This comparative example provides a heavy oil cracking catalyst, and its preparation method is as follows:
[0179] 0.87 kg kaolin (on dry basis), 0.45 kg aluminum sol (on alumina basis), 0.12 kg pseudo-boehmite (on dry basis), and 30 g cerium oxide were added to a beating tank for beating, and then 6 mL hydrochloric acid was added, stirred for 0.5 h, and aged at 60° C. for 0.5 h;
[0180] 1.5 kg of GUSY-1 molecular sieve (dry basis), 101.7 g of yttrium nitrate and 2.35 kg of deionized water were mixed and beaten for 1 hour, and then added to the first step beating tank, and then 15 g of carboxymethyl cellulose was added, and the beating was performed for 0.5 hour. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst microspheres;
[0181] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the heavy oil cracking catalyst DCAT-9.
[0182] The composition of the heavy oil cracking catalyst DCAT-9 is: 29wt% kaolin (dry basis), 4wt% alumina from pseudo-boehmite, 15wt% alumina from aluminum sol, 50wt% GUSY-1 molecular sieve (dry basis), 1wt% yttrium oxide from yttrium nitrate, 1wt% cerium oxide, and the solid content of the catalyst gel is 34%.
[0183] Test Example 1
[0184] The heavy oil cracking catalysts CAT-1, CAT-2, CAT-3, etc. prepared in Examples 1-7 and the comparative catalysts DCAT-1, DCAT-2, DCAT-3, etc. prepared in Comparative Examples 1-9 were subjected to analytical tests on anti-wear performance and pore volume. The test results are shown in Table 1.
[0185] Table 1 Performance test results of catalysts CAT-1, CAT-2, CAT-3, etc. and comparative catalysts DCAT-1, DCAT-2, DCAT-3, etc.
[0186]
[0187]
[0188] The results in Table 1 show that, compared with the comparative catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-6 and DCAT-8 prepared in Comparative Examples 1, 2, 3, 6 and 8, the heavy oil cracking catalysts CAT-1 to CAT-7 prepared in Examples 1 to 7 of the present invention have a smaller wear index, better anti-wear performance and a larger pore volume; compared with the comparative catalyst DCAT-5 prepared in Comparative Example 5, although the anti-wear performance of DCAT-5 and the heavy oil cracking catalyst CAT-3 prepared in Example 3 of the present invention can meet the requirements for catalyst use (generally the wear index should be less than 3.5%), the catalyst CAT-3 of the present invention has a larger pore volume. In Table 1, the wear indexes of DCAT-4, DCAT-7 and DCAT-9 are too high to meet the use requirements of the catalyst (generally the wear index should be lower than 3.5%); compared with DCAT-4, the catalyst CAT-1 has a low wear index and good anti-wear performance; compared with DCAT-7, the catalyst CAT-5 has a low wear index and good anti-wear performance; compared with DCAT-9, the catalyst CAT-7 has a low wear index and good anti-wear performance.
[0189] Test Example 2
[0190] This test example is used to evaluate the performance of the heavy oil cracking catalysts of Examples 1-3.
[0191] The heavy oil cracking catalysts CAT-1, CAT-2, CAT-3 prepared in Examples 1, 2, and 3 and the comparative heavy oil cracking catalysts DCAT-1, DCAT-2, DCAT-3, and DCAT-5 prepared in Comparative Examples 1, 2, 3, and 5 were subjected to aging treatment at 800°C and 100% water vapor for 17 h, respectively. The catalytic cracking reaction performances were evaluated on a heavy oil micro-reactor evaluation device (ACE) using the crude oil processed by the 3 million tons / year catalytic cracking unit of Lanzhou Petrochemical Company as the crude oil.
[0192] The evaluation results are shown in Table 2.
[0193] In Table 2, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.
[0194] Table 2 Evaluation results of reaction selectivity of heavy oil cracking catalysts of Examples 1-3, Comparative Examples 1-3, and Comparative Example 5
[0195]
[0196]
[0197] The results in Table 2 show that compared with the comparative catalytic cracking catalyst DCAT-2, the reaction conversion rate of the catalyst CAT-2 prepared in Example 2 increased by 0.62 percentage points, the total liquid yield (liquefied gas + gasoline + diesel) increased by 1.37 percentage points, the heavy oil yield decreased by 0.67 percentage points, the coke yield decreased by 0.65 percentage points, and the coke factor decreased, showing excellent heavy oil conversion and reduced coking characteristics. Compared with the comparative catalyst DCAT-3, the reaction conversion rate of the catalyst CAT-2 prepared in Example 2 increased by 2.19 percentage points, the total liquid yield (liquefied gas + gasoline + diesel) increased by 3.02 percentage points, the coke yield decreased by 1.10 percentage points, and the coke factor decreased. Compared with the comparative catalyst DCAT-5, the reaction conversion rate of the catalyst CAT-3 prepared in Example 3 increased by 1.93 percentage points, the total liquid yield (liquefied gas + gasoline + diesel) increased by 2.11 percentage points, the coke yield decreased by 0.89 percentage points, and the coke factor decreased.
[0198] Compared with the comparative heavy oil cracking catalysts DCAT-1, DCAT-2, DCAT-3 and DCAT-5 prepared in Comparative Examples 1, 2, 3 and 5, the reaction conversion rate of the heavy oil cracking catalysts CAT-1, CAT-2 and CAT-3 of the present invention is improved, the heavy oil yield is reduced, and the coke factor is reduced. This shows that the use of the heavy oil cracking catalyst of the present invention can promote the efficient conversion of heavy oil, reduce the tendency to form coke, and improve the selectivity of the catalytic cracking reaction.
Claims
1. A heavy oil cracking catalyst, which, based on the weight of the heavy oil cracking catalyst being 100%, comprises: 0-10% of ZSM-5 molecular sieve on a dry basis, 15-50% of Y-type molecular sieve on a dry basis, 10-55% of clay on a dry basis, 0-30% of pseudo-boehmite on a dry basis, 4-70% of titanium-containing composite binder on a dry basis, 0-15% of binder on an oxide basis, 0-30% of inorganic oxide carrier material on an oxide basis, and 0.2-5% of modified metal compound on an oxide basis; in, The preparation method of the titanium-containing composite binder comprises the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the above mixture at 40-120° C. for 0.5-6 hours to obtain the titanium-containing composite binder; Taking the dry basis of the titanium-containing composite binder as 100%, the composition of the titanium-containing composite binder comprises 7-45 wt % titanium calculated as oxide, 0.6-40 wt % aluminum calculated as oxide, and 30-92 wt % silicon calculated as oxide.
2. The heavy oil cracking catalyst according to claim 1, wherein Taking the weight of the heavy oil cracking catalyst as 100%, the composition thereof comprises: 1-8% of ZSM-5 molecular sieve calculated on a dry basis, 20-45% of Y-type molecular sieve calculated on a dry basis, 10-45% of clay calculated on a dry basis, 5-25% of pseudo-boehmite calculated on a dry basis, 6-55% of titanium-containing composite binder calculated on a dry basis, 3-15% of binder calculated on an oxide basis, 2-15% of inorganic oxide carrier material calculated on an oxide basis, and 0.5-3% of modified metal compound calculated on an oxide basis.
3. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The solid content of the titanium-containing composite binder is 10-45wt%; Preferably, based on 100% dry weight of the titanium-containing composite binder, the composition of the titanium-containing composite binder comprises 7-30 wt % titanium calculated as oxide, 8-40 wt % aluminum calculated as oxide, and 35-70 wt % silicon calculated as oxide.
4. The heavy oil cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the mixed raw materials also include a dispersant; based on the dry basis of the titanium-containing composite binder being 100%, the content of the dispersant is less than 10%.
5. The heavy oil cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the titanium tetrachloride solution is titanium tetrachloride waste liquid; the titanium tetrachloride waste liquid is titanium tetrachloride-containing waste liquid generated in the preparation process of polypropylene catalyst.
6. The heavy oil cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
7. The heavy oil cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the calcination is performed at 400-900° C. for 0.5-6 h; Preferably, the preparation method of the titanium-containing composite binder comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the titanium-containing composite binder.
8. The heavy oil cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8. Preferably, the pH value of the reaction system is adjusted to 0.5-8 by using an alkaline substance; Preferably, in step (1), the clay is crushed to an average particle size D(v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
9. The heavy oil cracking catalyst according to claim 1 or 2, wherein: Calculated as oxide, the ZSM-5 molecular sieve contains 0.2-6% phosphorus and 0-5% of a second element, wherein the second element includes one or a combination of two or more of iron, zinc, magnesium, calcium, titanium, zirconium, lanthanum, cerium and yttrium.
10. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The Y-type molecular sieve includes one or a combination of two or more of HY, NH4Y, hydrothermal ultra-stable Y molecular sieve, silicon tetrachloride vapor phase ultra-stable Y molecular sieve, rare earth-containing Y-type molecular sieve, and phosphorus-modified ultra-stable Y molecular sieve; the rare earth-containing Y-type molecular sieve includes one or a combination of two of rare earth-modified ultra-stable Y molecular sieve and phosphorus- and rare earth-modified ultra-stable Y-type molecular sieve.
11. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
12. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The inorganic oxide carrier material includes one or a combination of two or more of white carbon black, an alumina material containing a Brønsted acid center, and a silicon-aluminum material containing a Brønsted acid center.
13. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The modified metal compound includes one or a combination of two or more of the oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of zinc, magnesium, calcium, titanium, zirconium, lanthanum, cerium and yttrium.
14. The heavy oil cracking catalyst according to claim 1 or 2, wherein: The composition of the heavy oil cracking catalyst also includes a pore structure improver; the weight of the pore structure improver is 0.1-10% of the total weight of the heavy oil cracking catalyst; Preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
15. The method for preparing the heavy oil cracking catalyst according to any one of claims 1 to 14, comprising the following steps: (1) mixing and slurrying the ZSM-5 molecular sieve, Y-type molecular sieve, clay, pseudo-boehmite, inorganic oxide carrier material, titanium-containing composite binder, binder, and modified metal compound to obtain a slurry; (2) spray-drying the slurry to form a catalyst, then calcining and solidifying it, washing and reducing sodium, and drying it to obtain the heavy oil cracking catalyst; Preferably, the average particle size D (v, 0.5) of the slurry in step (2) is less than 4 μm; Preferably, the ZSM-5 molecular sieve is a mesoporous ZSM-5 molecular sieve.
16. The preparation method according to claim 15, wherein: The pseudo-boehmite is peptized by adding acid and then aging at 40-90° C. for 0.5-3 hours before use. In the process of peptizing the pseudo-boehmite by adding acid, the acid is an inorganic acid.
17. The preparation method according to claim 15, wherein: The pseudo-boehmite is first mixed with a titanium-containing composite binder, aged at 40-90° C. for 0.5-3 hours, and then used for peptization.
Citation Information
Patent Citations
Method for improving B acid content of ZSM-5 molecular sieve and realizing yield increase of light olefin
CN102114429B
Propylene polymerization catalyst
CN102336851B
A fluid catalytic cracking catalyst and its preparation method
CN105618107B
A polypropylene catalyst component, preparation method and catalyst thereof
CN107434832B
A TiO2 sol and a catalytic cracking catalyst and their preparation methods
CN107866211B